Health Effects of LED Light Exposure among College Students: Insights from Sidama Regional State, Ethiopia - Zeleke Heramo , Dr. Genius Walia (South Eastern European Journal of Public Health, 2025)
This study investigates the health effects of LED light exposure among college students in Sidama Regional State, Ethiopia, employing a cross-sectional survey design with a quantitative approach. Data were collected from 377 college students using self-administered questionnaire, and the results were analyzed using mean, standard deviation, and Analysis of Variance (ANOVA). The findings highlight significant negative effects of increased exposure to LED light sources, particularly the blue-rich spectrum emitted by devices such as smartphones, televisions, and computer screens. The study reveals that prolonged exposure disrupts circadian rhythms by inhibiting melatonin production, leading to sleep disturbances, poor sleep quality, and daytime fatigue. Additionally, excessive LED light exposure contributes to visual discomfort and potential retinal damage, which may result in long-term effects such as retinal degeneration. The study further identifies a correlation between prolonged screen time and mental health issues, including anxiety, stress, and depression. These findings underscore the importance of addressing the health risks associated with LED light exposure among college students.